Development of Mini-Barcode Based on Chloroplast Genome and Its Application in Metabarcoding Molecular Identification of Chinese Medicinal Material Radix Paeoniae Rubra (Chishao) - Yang, Xia; Yu, Xiaolei; Zhang, Xiaoying; Guo, Hua; Xing, Zhimei; Xu, Liuwei; Wang, Jia; Shen, Yuyan; Yu, Jie; Lv, Pengfei; Wang, Yuefei; Liu, Mengyang; et al. (Frontiers in Plant Science, 2022)
Radix Paeoniae Rubra (Chishao), a typical multi-origin Chinese medicinal material, originates from the dried roots of Paeonia lactiflora or P. veitchii. The previous study suggested that these two commonly used Chishao showed variation in their chemical compositions and clinical efficacies. Therefore, accurate identification of different Chishao species was of great significance for the guide of clinical medication, and timely treatment of patients. In this study, the chloroplast genome sequences of P. lactiflora and P. veitchii were obtained by next-generation sequencing (NGS) technology, and then the hypervariable regions were selected to design two mini-barcode candidates for species identification. Combined with DNA metabarcoding technology, we performed qualitative and quantitative analysis on the artificially mixed samples of P. lactiflora and P. veitchii and evaluated the identification ability of these mini-barcode candidates. Furtherly, the mini-barcode with good performance was applied to distinguish the Chinese patent medicine “cerebral thrombosis tablets” containing Chishao. The results indicated that the chloroplast genomes of P. lactiflora and P. veitchii were 152,750 and 152,527 bp, respectively. As published previously, they exhibited a typical quadripartite structure including a large single-copy region (LSC), a small single-copy region (SSC) and a pair of inverted repeat regions (IRs). The nucleotide polymorphism analysis revealed seven variable protein-coding regions as petL, psaI, psbJ, rpl16, ycf1b, psaC, and ndhF, and two mini-barcodes were developed from ycf1b and ndhF respectively. The result suggested that both two mini-barcodes performed well distinguishing P. lactiflora from P. veitchii. Besides, P. lactiflora was the only raw material of Chishao in all collected “cerebral thrombosis tablets” samples. In general, this study has established a method to realize the qualitative and quantitative identification of Chishao as multi-origin Chinese medicinal materials, which can be applied to Chinese patent medicines containing Chishao.